PENGARUH MENONTON VIDEO DAKWAH GUS BAHA DAN USTADZ KHALID BASALAMAH TERHADAP TINGKAT RELIGIUSITAS PADA MASYARAKAT - Furqan MD, Muhammad; Ronaydi, Muhammad; Tamirano, Randi (Qaulan Baligha: Jurnal Ilmu Manajemen Dakwah, 2024)
This research was conducted to determine the influence of two preachers who are quite well known in society, namely Gus Baha and Ustadz Khalid Basalamah. In this research the author wants to see the influence of the da'wah they spread using preaching videos on the level of religiosity in society. Religiosity is certainly an important thing in an individual's life because religiosity is a belief that contains values ​​in living life. This research uses quantitative methods with random sampling data collection techniques with the population being people who use social media to watch videos of the preaching of Gus Baha and Ustadz Khalid Basalamah. A sample of 121 respondents was collected. The results of the research show that watching Gus Baha and Ustadz Khalid Basalamah's Da'wah videos has an influence on the religiosity of society. The higher percentage level of influence when watching Gus Baha's preaching videos is based on the results of the Reliability test which produced Gus Baha's Cronbach's Alpha of 0.963 > 0.60 while Usadz Khalid Basalamah's Cronbach's Alpha was 0.954 > 0.60. The entire questionnaire and reliability calculations in this study can be declared valid and reliable.